A Review of Heat and Fluid Flow Characteristics in Microchannel Heat Sinks - Coşkun, Turgay; Coşkun, Turgay; Çetkin, Erdal; Çetkin, Erdal (John Wiley and Sons Inc., 2020)
Heat transfer and flow characteristic in microchannel heat sinks (MCHS) are extensively studied in the literature due to high heat transfer rate capability by increased heat transfer surface area relative to the macroscale heat sinks. However, heat transfer and fluid flow characteristics in MCHS differ from conventional ones because of the scaling effects. This review summarizes the studies that are mainly based on heat transfer and fluid flow characteristic in MCHS. There is no consistency among the published results; however, everyone agrees on that there is no new physical phenomenon in microscale that does not exist at macroscale. Only difference between them is that the effect of some physical phenomena such as viscous dissipation, axial heat conduction, entrance effect, rarefaction, and so forth, is negligibly small at macroscale, whereas it is not at microscale. The effect of these physical phenomena on the heat transfer and flow characteristics becomes significant with respect to specified conditions such as Reynolds number, Peclet number, hydraulic diameter, and heat transfer boundary conditions. Here, the literature was reviewed to document when these physical phenomena become significant and insignificant.
Keywords: Axial heat conduction; Continuum; Entrance effect; Microchannel heat sink; Viscous dissipation